2012
DOI: 10.1080/11250003.2012.687777
|View full text |Cite
|
Sign up to set email alerts
|

Diet of the introduced pikeperchSander lucioperca(L.) (Osteichthyes, Percidae) in a recent colonised reservoir in south-western Iberian Peninsula

Abstract: The present study examines the diet of pikeperch (Sander lucioperca) in Iberian freshwaters. Food habits of Sander lucioperca were studied based on stomach content analyses of 376 specimens (12.22-52.52 cm total length) collected in 2009 on a south-western Iberian reservoir. A total of 265 stomachs (79.52%) contained food, and fifteen taxonomic levels of prey were identified. The most important prey was fish according to the Relative Importance Index (IRI). Trophic level analysis revealed that S. lucioperca is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 37 publications
5
8
0
Order By: Relevance
“…However, the results presented here are generally consistent with other studies conducted in Spain and France, supporting the current observed patterns adjusted to Iberian watersheds [36,60]. The sampling period of this study might have influenced the results; however, most of the studied populations were lentic ones, related to reservoirs that are more stable environments with a limited community seasonal change [36]. Specifically, it would be important to widen the study period to encompass the entire year in riverine populations, to evaluate the predation effect on anadromous fish that spawn during the winter months [20].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, the results presented here are generally consistent with other studies conducted in Spain and France, supporting the current observed patterns adjusted to Iberian watersheds [36,60]. The sampling period of this study might have influenced the results; however, most of the studied populations were lentic ones, related to reservoirs that are more stable environments with a limited community seasonal change [36]. Specifically, it would be important to widen the study period to encompass the entire year in riverine populations, to evaluate the predation effect on anadromous fish that spawn during the winter months [20].…”
Section: Discussionsupporting
confidence: 93%
“…The current work evaluates pikeperch dietary patterns from different populations that were collected across a wide spatial gradient, using different methodologies, encompassing distinct months and involving a limited number of individuals in some populations. However, the results presented here are generally consistent with other studies conducted in Spain and France, supporting the current observed patterns adjusted to Iberian watersheds [36,60]. The sampling period of this study might have influenced the results; however, most of the studied populations were lentic ones, related to reservoirs that are more stable environments with a limited community seasonal change [36].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In general, predation by non-native fish could affect the population structures and dynamics of native fish species in the Iberian Peninsula [95]. Some studies from other Iberian rivers confirmed the inclusion of different barbel species in the diet of top predator fish such as E. lucius [100,101] and S. Lucioperca [102]. Predatory fish (E. lucious, S. lucioperca and M. salmoides) showed a higher occurrence in the lower reaches of the study area.…”
Section: Discussionmentioning
confidence: 99%